The Divergence of Experts’ Views on a Mentor Competence Profile - Hašková, Alena; Guziurová, Tereza; Klimszová, Slavomíra; Malá, Eva (Journal of Education Culture and Society, 2023)
Aim. The paper focuses on the divergence of views of experts from four European educational institutions on key competences, which would become the basis for a successful performance of a mentor position. They should be taken as the key items of a mentor competence profile.Methods. A panel discussion – specifically, a focus group interview as its alternative form – was used to determine how the experts assessed particular competences of the mentor competence profile, i.e. to identify which competences they considered to be the key ones of the mentor competence profile. The panel discussion was led by six focus groups, members of which were experts representing four different countries from six universities: two from Slovakia and the Czech Republic, and one from Hungary and Serbia.Results. The intention of the conducted panel discussion was to find a common view and consensus on the key competences required for a successful performance of the mentor position. However, the results of the panel discussion showed a significant divergence of the opinions on the fundamental mentor competences depending on the country the experts were from. Differences in the views on the issue examined by experts representing different institutions from the same country also occurred, but proved to be inconclusive. Conclusion. Mentoring is currently considered one of the most important means of developing pedagogical competences of future and novice teachers. The results of the conducted panel discussion may contribute to the creation of a platform on which an adequate professional mentor training can be designed.